MATURATION AND HARVEST OF SEED DE Amburana cearensis (Allem.) A.C. Smith. - Lopes, Izabela Souza (2014)
http://dx.doi.org/10.5902/1980509815734Studies about the maturation of seeds are essential to guide the ideal time of harvest, to assist the drying process planning, for storage and quality control. Therefore, the work aimed to know the appropriate time to harvest seeds from Amburana cearensis (Allem.) A. C. Smith. The fruits were collected in the city of Malta, in Paraíba state, and then taken to the seed laboratory at the Universidade Federal de Campina Grande, where the analyses and the germination tests were carried out. In each of the six harvests, held weekly, fruits and seeds were evaluated for staining, biometrics and water content addition of the dry mass, germination and vigor of seeds. The experimental design was completely randomized with four replications of 25 seeds each. The revealed results have found that 54 days after anthesis, this stadium prior to dehiscence of fruits, these were dark brown color, wrinkled and with cracks at the apex, while the seeds in the sweet spot of physiological ripeness, black coloring, germination of 94,0%; 3,0% of abnormal seedlings and dead seed for 1.0% in the northeastern semi-arid conditions, it is recommended to harvest of the fruits to 54 days after anthesis when they presented a dark brown color and wrinkled apex with cracks, once 63 days after anthesis there is the natural dispersion of seeds.